2023
DOI: 10.1371/journal.pone.0289310
|View full text |Cite
|
Sign up to set email alerts
|

Admissions to psychiatric inpatient services and use of coercive measures in 2020 in a Swiss psychiatric department: An interrupted time-series analysis

Abstract: Background The CoVID pandemic and the associated lockdown had a significant impact on mental health services. Inpatient services faced the challenge of offering acute psychiatric while implementing strict infection control measures. There is, however, a lack of studies investigating the use of coercive measures during the pandemic and their relation to hospitalizations and symptom severity. Aims To investigate the effects of the CoVID outbreak on psychiatric admissions, use of seclusion and symptom severity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
(54 reference statements)
2
3
0
Order By: Relevance
“…45,46 The annual trend of admissions divided between VHs and IHs shows a progressive sharp decrease in VHs admissions, concurrent with the pandemic, while the number of IHs admissions remained relatively stable over time, surpassing the number of VHs admissions in absolute terms by the year 2022. This result clearly highlights that, despite the emergency situation, there was a portion of individuals whose admission was necessary and urgent due to acute and severe conditions, and this is in line with national and international studies, 42,[47][48][49][50] which reported a similar trend during pandemic with an increase in involuntary hospitalizations and coercive measures in Psychiatry. In accordance with most authors, we can hypothesize that, during pandemic, reduced availability of outpatient service activities and, at the same time, stressful conditions of isolation as well as reduced treatment of non-COVID-19 related disorders could have…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…45,46 The annual trend of admissions divided between VHs and IHs shows a progressive sharp decrease in VHs admissions, concurrent with the pandemic, while the number of IHs admissions remained relatively stable over time, surpassing the number of VHs admissions in absolute terms by the year 2022. This result clearly highlights that, despite the emergency situation, there was a portion of individuals whose admission was necessary and urgent due to acute and severe conditions, and this is in line with national and international studies, 42,[47][48][49][50] which reported a similar trend during pandemic with an increase in involuntary hospitalizations and coercive measures in Psychiatry. In accordance with most authors, we can hypothesize that, during pandemic, reduced availability of outpatient service activities and, at the same time, stressful conditions of isolation as well as reduced treatment of non-COVID-19 related disorders could have…”
Section: Discussionsupporting
confidence: 87%
“… 55 One study showed that the COVID-19 pandemic in 2020 was associated with a significant decrease in the number of hospital admissions and a greater use of seclusion. 50 These results were confirmed by another study, which reported that while voluntary cases decreased considerably during the pandemic, involuntary cases increased slightly, indicating a deterioration in treatment quality during the pandemic. 48 Another study further confirmed these results during the COVID-19 pandemic, 49 suggesting an overall increased severity of mental disorders during the pandemic, due to deferrals of admissions or reduction of mental healthcare services interventions.…”
Section: Discussionsupporting
confidence: 57%
“…However, it is currently unknown whether R/S intervention use changed in other clinical settings, such as EDs, which saw dramatic changes in service provision during the pandemic [4,[10][11][12]. Similarly, existing research has focused solely on R/S use for patients with MH issues [33][34][35][36][37][38][39][40][41], despite the fact that SU-related concerns increased on par with MH-related concerns during the pandemic [19][20][21][22][23][24][25][26] and are a known risk factor for the use of R/S interventions [42,43].…”
Section: Current Studymentioning
confidence: 99%
“…Similarly, a study of adult psychiatric admissions in Germany found that the number R/S events increased by almost 25% for patients who were voluntarily admitted, and 13% among those who were involuntarily admitted during the pandemic [ 40 ]. Finally, a study from the Department of Psychiatry at the Geneva University Hospital in Switzerland reported a slight increase in the number of seclusion events after COVID onset, despite a decrease in both voluntary and involuntary hospital admissions [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data on ED and hospital admissions for psychiatric disorders during the pandemic remain inconsistent with the majority of studies conducted internationally. For example, the studies from Europe, UK, Australia, South Korea and Canada variably reported both increases or decreases in visits [7][8][9][10][11][12][13][14][15][16][17][18]. In the United States, there were inconsistent and limited data on ED visits and admissions for adults in Midwest, rural areas of West Texas, urban Kentucky and New York City as well [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%